Ownership structure, legal environment and timeliness in loss recognition in China. - Liang, Chen. (2008)
This study investigates the effect of accounting reform on the timeliness in loss recognition by incorporating the unique institutional infrastructures in China. Our results show that the inefficient state ownership and weak legal environment are two key factors that limit the effectiveness of the accounting reform. As state-owned firms are faced with non-profit maximization goals and poor monitoring by shareholders, creditors, and auditors, they are less timely in recognizing losses compared to non-state-owned firms. Furthermore, accounting reform results in greater timeliness in loss recognition for non-state-owned firms compared to state-owned firms. However, our results also show that the inefficiency of state ownership could be mitigated by the stricter enforcement of laws. The gap in the timeliness in loss recognition between state-owned firms and non-state-owned firms in regions with stringent legal environment is smaller than that in provinces with poor legal infrastructure.